Associations between obesity and cognition in the pre‐school years. (6th December 2015) - Martin, Anne; Booth, Josephine N.; Young, David; Revie, Matthew; Boyter, Anne C.; Johnston, Blair; Tomporowski, Phillip D.; Reilly, John J.
Abstract : Objective: To test the hypothesis that obesity is associated with impaired cognitive outcomes in the pre‐school years. Methods: Associations were examined between weight status at age 3‐5 years and cognitive performance at age 5 years. Cognitive outcome measures were tests of pattern construction (visuospatial skills), naming vocabulary (expressive language skills), and picture similarity (reasoning skills). The sample was the UK Millennium Cohort Study ( n = 12, 349 participants). Results: Boys with obesity at 3 years had significantly lower performance in pattern construction at age 5 years compared to those of a healthy weight, even after controlling for confounders ( β = −0.029, P = 0.03). Controlling for confounders, boys who developed obesity between the ages of 3 and 5 years had lower scores in pattern construction ( β = −0.03, P = 0.03). "Growing out" of obesity had a positive association with picture similarity performance in girls ( β = 0.03, P = 0.04). Conclusions: Obesity in the pre‐school years was associated with poorer outcomes for some cognitive measures in this study. Stronger relationships between obesity and cognition or educational attainment may emerge later in childhood.